Herpes Simplex Virus 1 UL2 Inhibits the TNF-α–Mediated NF-κB Activity by Interacting With p65/p50 - Cai, Mingsheng; Liao, Zongmin; Zou, Xingmei; Xu, Zuo; Wang, Yuanfang; Li, Tong; Li, Yiwen; Ou, Xiaowen; Deng, Yangxi; Guo, Yingjie; Peng, Tao; Li, Meili (Frontiers in Immunology, 2020)
Herpes simplex virus 1 (HSV-1) is a large double-stranded DNA virus that encoding at least 80 viral proteins, many of which are involved in the virus-host interaction and are beneficial to the viral survival and reproduction. However, the biological functions of some HSV-1 encoded proteins are not fully understood. Nuclear factor κB (NF-κB) activation is the major antiviral innate response, which can be triggered by various signals induced by cellular receptors from different pathways. Here, we demonstrated that HSV-1 UL2 protein could antagonize the tumor necrosis factor-α (TNF-α)-mediated NF-κB activation. Co-immunoprecipitation assays showed that UL2 could interact with the NF-κB subunits p65 and p50, which also revealed the region of amino acids 9 to 17 of UL2 could suppress the NF-κB activation and interact with p65 and p50, and UL2 bound to the immunoglobulin-like plexin transcription factor functional domain of p65. However, UL2 did not affect the formation of p65/p50 dimerization and their nuclear localizations. Yet, UL2 was demonstrated to inhibit the NF-κB activity by attenuating TNF-α-induced p65 phosphorylation at Ser536, and therefore decreasing the expression of downstream inflammatory chemokine interleukin-8. Taken together, the attenuation of NF-κB activation by UL2 may contribute to the escape of host's antiviral innate immunity for HSV-1 during its infection.